Wavelengths: Implications of naturalistic psychedelic experiences on everyday life of Young Adults - Gunnarsson,Emma (2025)
Despite a drastic increase in psychedelic research in recent years, studies on younger populations are sparse. This qualitative study aims to explore perceived implications of naturalistic psychedelic experiences on young adults' daily life, self perception, and long term values as well as in which ways the experiences were integrated, or not, over time. Data was collected using semi structured interviews; the sample included five young adults ages 18-23 from Nordic countries who had used psychedelics within the past year. Inductive reflexive thematic analysis was used to analyze data where five themes were revealed; enhanced connection to the world, self, and others; the limbo between the altered psychedelic state and reality; a curious yet private practice of psychedelic use; reclaiming agency through personal values; and “aha-moments” of discovery. Depictions of heightened empathy, emotional expression, authenticity, and deeper alignment to personal values were narrated as well as alienation and difficulties integrating the experiences into everyday life. Availability of guidance was seen to be pivotal for successful integration. Findings from this study's sample suggest that psychedelics may function as a catalyst to psychological flexibility and alignment to personal values, but integration of these insights of experiential nature are contingent upon individual (set) and contextual factors (setting). This study highlights the possible importance for young adults using psychedelics to be informed with harm reduction strategies as well as integration support to minimize the risk of unfavorable outcomes of a naturalistic psychedelic experience.
Keywords: Adolescents; hallucinogens; altered states of consciousness; psychological transformation; naturalistic use; Tonåringar; hallucinogener; förändrade medvetandetillstånd; psykologisk transformation; naturalistisk användning